Social Media, Word of Mouth, and Consumer Purchase Decisions During COVID-19 At Viva City Cafe - Firdaus, Muhamad Fulaisum; Mahfudoh, Mahfudoh; inayatuddiniyah, Inayatuddiniyah (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the effect of social media and word of mouth on consumer purchasing decisions during the Covid-19 pandemic at Viva City Cafe. The method used is distributing questionnaires to all customers who have purchased products that cannot be counted. The results showed that there was no significant influence between social media on consumer purchasing decisions, there was a significant influence between word of mouth on consumer purchasing decisions, and there was a significant influence difference between social media and word of mouth on consumer purchasing decisions. This research is relatively new and has yet to be carried out by many previous researchers.